Sistema de Control de Inventarios de la Empresa Distribuidora Importadora Dipor S.A. - González Fernández, Joel (2018)
The present case study, based on the INVENTORY CONTROL SYSTEM, was developed at La Distribuidora Importadora Dipor SA located in the city of Babahoyo, starting its commercial operations on June 24, 2011, this is dedicated to the distribution of products from mass consumption (dairy and its derivatives, jellies, plastic products, etc.), in this way identify the problems within it, pretending to show the areas that are included in the mismanagement of inventory records. According to the research sub-line FINANCIAL MANAGEMENT AND SOCIAL COMMITMENT, within La Distribuidora Importadora Dipor SA, branch Babahoyo, the problems within the winery area will be detected, significantly affecting other areas of the winery, since all this entails the inadequate management of the inventory control of their products, although the distributor has programs and inventory control systems, the misuse of the manual affects their movements due to lack of training on the part of their employees, not only the one who handles it but also of who receives and dispatches the products. We can mention that due to the inadequate control of the inventory they are affected not only in the warehouse area, being the most vulnerable but also in the control areas of the company as the administrative area since this area performs the accounting movements of the products, being One reason is the lack of information on the part of the warehouse area employees. When carrying out the inventory the distributor closes its activities once a month, which alters them considerably since this is not efficient and reliable for the company, this is where the loss of products is, due to the fact that they close their activities, but still the merchandise is still manipulated.